Accessing camera trap survey feasibility for estimating Blastocerus dichotomus (Cetartiodactyla, Cervidae) demographic parameters - Peres, Pedro Henrique F. [UNESP]; Polverini, Maxihilian S. [UNESP]; Oliveira, Marcio L. [UNESP]; Duarte, Jose Mauricio B. [UNESP] (Fundacao Zoobotanica Rio Grande Sul, Museu Ciencias Naturais, 2017)
Demographic information is the basis for evaluating and planning conservation strategies for an endangered species. However, in numerous situations there are methodological or financial limitations to obtain such information for some species. The marsh deer, an endangered Neotropical cervid, is a challenging species to obtain biological information. To help achieve such aims, the study evaluated the applicability of camera traps to obtain demographic information on the marsh deer compared to the traditional aerial census method. Fourteen camera traps were installed for three months on the Capao da Cruz floodplain, in state of Sao Paulo, and ten helicopter flyovers were made along a 13-kilometer trajectory to detect resident marsh deer. In addition to counting deer, the study aimed to identify the sex, age group and individual identification of the antlered males recorded. Population estimates were performed using the capture-mark-recapture method with the camera trap data and by the distance sampling method for aerial observation data. The costs and field efforts expended for both methodologies were calculated and compared. Twenty independent photographic records and 42 sightings were obtained and generated estimates of 0.98 and 1.06 ind/km(2), respectively. In contrast to the aerial census, camera traps allowed us to individually identify branch-antlered males, determine the sex ratio and detect fawns in the population. The cost of camera traps was 78% lower but required 20 times more field effort. Our analysis indicates that camera traps present a superior cost-benefit ratio compared to aerial surveys, since they are more informative, cheaper and offer simpler logistics. Their application extends the possibilities of studying a greater number of populations in a long-term monitoring.
Keywords: Aerial survey; capture-recapture; distance sampling; population estimate; sex ratio